Drought Impacts Assessment on Afghanistan - Peroz, Sharifullah (Journal of Natural Sciences – Kabul University, 2026)
Afghanistan is a vulnerable country towards drought. For this purpose, the research was conducted to analyses the negative impacts and level of this impacts on the country. The country’s situation was assessed by using a comprehensive review. The result show that Afghanistan is highly vulnerable to meteorological and hydrological droughts. And the water storage capacity of the country is very low. Since 2000 this country was suffered by devastating droughts six time. The problem that this country is facing due to sever drought are: threat of desertification, severity of floods, shortage of agriculture products, famine, poverty, migration, decrease in the income of farmers, lake of attention to invest in agriculture sector and animal extinction. To solve this problem, the government should find and store resistant agriculture varieties to cope against drought, setup multi sectorial plans for drought management and establish new assessment and early warning system for drought and famine.